Notes on the Caribbean orchid flora. V. New species, combinations and records - Ackerman, James D. (Lankesteriana: International Journal on Orchidology, 2016)
Three species of Orchidaceae are described as new to science: a Telipogon and a Lankesterella from the Dominican Republic and an Encyclia from Cuba. Telipogon niri is based on material collected by Donald Dod from the Cordillera Central A rare species, T. niri was previously recognized as Stellilabium minutiflorum (Kraenzl.) Garay, a distinct species from Central America. The generic name has changed due to unequivocal molecular evidence offered by Norris Williams, and the specific epithet honors Dr. Mark Nir, an avid student of Caribbean orchids. Lankesterella glandula is also based on material collected by Dod from the Cordillera Central. Thus far known only from the type collection, it is the second representative of the genus in Hispaniola. Encyclia monteverdensis is described from 19th century Charles Wright collections from Monte Verde, Cuba. The combination, Dendrophylax filiformis (Sw.) Carlsward & Whitten, suffers as a later homonym and is replaced by the next available name in the new combination Dendrophylax mon- teverdi (Rchb. f.) Ackerman & Nir. Cyclopogon miradorensis Schltr. is reported for the island of Dominica; Cranichis ricartii Ackerman is noted for the island of Guadeloupe; Cranichis ovata Wickstr. and Psilochilus macrophyllus (Lindl.) Ames are noted for Montserrat; and Trinidad is another locality for C. ovata. In addi- tion, Eurystyles domingensis Dod and two Malaxis species are added to the Cuban flora: M. apiculata Dod and M. hispaniolae (Schltr.) L.O. Williams.